Optimization of high strength concrete with construction and demolition waste. Issue 1 (November 2020) - Geetha, S; Selvakumar, M; Muthulakshmi, S
Abstract: The development in the Infrastructure Sector has led to a revolution in the Construction Industry with fast track projects. Hence the use of prefabricated construction is gaining importance in India in the recent days. The structural elements like beams, columns and wall panels are fabricated in a factory and assembled at the site. The concrete used in the fabrication of these members are conventional concrete with density range 2400-2500 kg/m 3 . The transport, handling and erection of these members involve large machineries. Moreover due to the use of conventional concrete the self weight of the structure also increases leading to large column size and foundations. Hence this work is based in optimizing reactor powder with mineral admixtures, construction and demolition waste and steel fibres that can be used in precast construction. The compressive strength achieved is 63.12 Mpa, flexural strength is 6.21 and tensile strength is 6.38MPa. Rapid chloride penetration test (RCPT) was done to test the durability of the concrete and it was found to be 469 coulombs which proved it to be resistant to chloride penetration.